Economic impact of venous thromboembolism after hip and knee arthroplasty: potential impact of rivaroxaban. (June 2011) - Friedman, Richard J; Sengupta, Nishan; Lees, Michael
The number of total hip and knee arthroplasties is increasing, with a consequent rise in the number of patients at risk of venous thromboembolism. Each such event is associated with the risk of morbidity and mortality, plus substantial healthcare costs. Consequently, the American College of Chest Physicians guidelines recommend low-molecular-weight heparins, fondaparinux or vitamin K antagonists (usually warfarin) after total hip and knee arthroplasty. However, such agents are also associated with healthcare costs for administration and monitoring. New oral anticoagulants in development may reduce post-arthroplasty symptomatic thromboembolic events and produce potential savings for the healthcare system. This brief article outlines such potential savings with rivaroxaban based on the results of the REgulation of Coagulation in ORthopaedic surgery to prevent Deep vein thrombosis and pulmonary embolism (RECORD) program.